Corrosion Inhibition of Carbon Steel Using (Arginine–Levofloxacin–Metal) Complexes in Acidic Media - Hanan Emrayed; Hamad Hasan; Raad Liser (AlQalam Journal of Medical and Applied Sciences, 2025)
This work investigates the inhibition efficiency of carbon steel corrosion in 1 M hydrochloric acid using synthesized complexes of levofloxacin, arginine, and metal ions Cu²⁺, Mn²⁺, Cd²⁺. The study relies solely on weight loss measurements to evaluate corrosion rates at different concentrations and temperatures (25–45 °C). The results revealed that the Cu–levofloxacin–arginine complex provided the highest inhibition efficiency of 97.3% at 298 0K, significantly outperforming the Mn and Cd analogs. The inhibition mechanism was attributed to surface adsorption, which followed the Langmuir isotherm model, indicating monolayer coverage. These findings suggest that the copper-based complex is a promising, eco-friendly inhibitor for carbon steel in acidic environments.